Remote Health Watchdog Framework for Seizure Patient Using Electronic Sensors - Devi Majety, Vasumathi; G.Murali, Dr (International Journal of Engineering and Technology, 2018)
Epilepsy is due to the neurological disorder of a patient which makes the patient uncontrolled and makes unconscious. The patient should get support through an ongoing framework. The brilliant epilepsy recognition and ready framework is a propelled innovation by which an electronic device is introduced. Utilizing that pack, the life of the individual who is truly affecting with the condition can be anticipated. As per World Health Organization (WHO), epilepsy is a standout amongst the most well-known essential sicknesses of the focal sensory system around the world, which is exasperated by the sudden variable that portrays the event of an epileptic occasion. In this manner, the capacity to recognize scene preceding its beginning is introduced as a relief variable to the upsetting effects that emerge from this situation. The casing will be tolerable, confirms the condition and also alerts to the the family doctor. To realize all the above plan, mainly utilized four modules: three sensors, data analysis and ARDUINO module with GSM and GPRS module.Â Â